Understanding the effects of legalizing undocumented immigrants - Joan Monras; Javier Vázquez-Grenno; Ferran Elias (W.E. Upjohn Institute for Employment Research, 2018)
This paper investigates the consequences of the legalization of around 600,000 immigrants by the unexpectedly elected Spanish government of Zapatero following the terrorist attacks of March 2004 (Garcia-Montalvo, 2011). Using detailed data from payroll-tax revenues, we estimate that each newly legalized immigrant increased local payroll-tax revenues by 4,189 euros on average. This estimate is only 55 percent of what we would have expected from the size of the influx of newly documented immigrants, which suggests that newly legalized immigrants probably earned lower wages than other workers and maybe affected the labor-market outcomes of those other workers. We estimate that the policy change deteriorated the labor-market outcomes of some low-skilled natives and immigrants and improved the outcomes of high-skilled natives and immigrants. This led some low-skilled immigrants to move away from high-immigrant locations. Correcting for internal migration and selection, we obtain that each newly legalized immigrant increased payroll-tax revenues by 4,801 euros, or 15 percent more than the estimates from local raw payroll-tax revenue data. This shows the importance of looking both at public revenue data and the labor market to understand the consequences of amnesty programs fully.
Keywords: F22; J32; J61; R11; 330; Immigration; undocumented immigrants; public policy evaluation